2008
DOI: 10.1136/pgmj.2008.068320
|View full text |Cite
|
Sign up to set email alerts
|

Bubble trouble: a review of diving physiology and disease

Abstract: Exposure to the underwater environment for recreational or occupational purposes is increasing. Approximately 7 million divers are active worldwide and 500 000 more are training every year. Diving related illnesses are consequently an increasingly common clinical problem with over 1000 cases of decompression illness reported annually in the USA alone. Divers are exposed to a number of physiological risks as a result of the hyperbaric underwater environment including: the toxic effects of hyperbaric gases, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 30 publications
1
66
0
2
Order By: Relevance
“…Neurons do not only show altered signal propagation properties along their axons or dendrites, but also a delay in the signal coupling across their synapses (Bryant and Blankenship, 1979;Sauter, 1979a,b;Dean and Mulkey, 2000). In networks with a small number of neurons, the electric activity was found to be reduced by the latter effect (Hills and Ray, 1977;Sauter, 1979a,b;Grossman and Kendig, 1988;Hamilton et al, 1995;Dean and Mulkey, 2000;Levett and Millar, 2008;Pendergast and Lundgren, 2009). These properties of nitrogen are probably the reasons for the similarity of the effects to an alcoholic stupor in the human brain, which led to the term "rapture of the deep" for the nitrogen narcosis (Behnke and Yarbrough, 1939;Baddeley et al, 1968;Roth and Seeman, 1972;Davis et al, 1972;Bennett, 1986).…”
Section: Introductionmentioning
confidence: 85%
“…Neurons do not only show altered signal propagation properties along their axons or dendrites, but also a delay in the signal coupling across their synapses (Bryant and Blankenship, 1979;Sauter, 1979a,b;Dean and Mulkey, 2000). In networks with a small number of neurons, the electric activity was found to be reduced by the latter effect (Hills and Ray, 1977;Sauter, 1979a,b;Grossman and Kendig, 1988;Hamilton et al, 1995;Dean and Mulkey, 2000;Levett and Millar, 2008;Pendergast and Lundgren, 2009). These properties of nitrogen are probably the reasons for the similarity of the effects to an alcoholic stupor in the human brain, which led to the term "rapture of the deep" for the nitrogen narcosis (Behnke and Yarbrough, 1939;Baddeley et al, 1968;Roth and Seeman, 1972;Davis et al, 1972;Bennett, 1986).…”
Section: Introductionmentioning
confidence: 85%
“…Death resulting from CAGE usually occurs after a rapid ascent within seconds or minutes after surfacing but may be prevented if rapid recompression is applied, although secondary deterioration is possible. Death may be preceded by convulsion, paralysis, unconsciousness and cardiac arrhythmia, all of which are unresponsive to resuscitation (Levett and Millar 2008;Vann et al 2009. Non-fatal CAGE is possible.…”
Section: Pulmonary Barotrauma and Arterial Gas Embolismmentioning
confidence: 99%
“…Venous gas bubbles may also reach the arterial system via a patent foramen ovale, because increased pulmonary pressure due to gas embolism in the lung produces a right-to-left intracardiac shunt. Divers with patent foramen ovales have a statistically significant higher incidence of serious cerebral or spinal DCS manifestations, but this is not a common cause of death (Saary and Gray 2001;Levett and Millar 2008).…”
Section: Diving Gas Problemsmentioning
confidence: 99%
“…More recently, it has been suggested that immune reactivity, stress responses, inflammatory reactions, microparticle generation, and endothelium dysfunction contribute to DCS pathogenic mechanisms (2,4,27). Intravascular bubbles may impose a stress to tissues (22) and affect both the blood vessel luminal surfactant layer and endothelial activation, resulting in subsequent (18) platelet and leukocyte aggregation, cytokine release, complement activation, and coagulation cascades (4,9,30). Additional observations implicating immune-mediated mechanisms in DCS susceptibility include altered TNF-␣ and IL-6 levels in a rat model of DCS (4) and a positive correlation between susceptibility to DCS and sensitivity to complement activation (30).…”
mentioning
confidence: 99%